A Rare Case of Squamous Cell Carcinoma arising in Mature Cystic Teratoma - Adhikari, Alisha; Sharma, Prashim; Singh, Mrinalini; Yadav, Nitesh (Birat Journal of Health Sciences, 2024)
Squamous  cell  carcinoma  (SCC)  arising  within  a  mature  cystic  teratoma  (MCT)  is  a  rare  neoplasm.  Though  it   is  a  malignant  tumour,  it  can  remain  clinically silent.  On  radiologic  examination  we  can  detect   the  size,  extent  of  the  tumour  and  whether  it  is  cystic  or  solid  neoplasm.  To  diagnose  malignancy  histopathologic  examination  is  needed  in  most  of  the  cases.  We  report  a  case  of  a  65-year-old  female  presenting  with  a  left  pelvic  mass.  The  mass  was  radiologically  suggestive  of  mature  cystic  teratoma.  However  on  histopathology  it  was  diagnosed  as  squamous  cell  carcinoma  arising  in  a  mature  cystic  teratoma.  This  case  underscores  the  importance  of  considering  malignant  transformation  in  seemingly  benign  ovarian  masses  and  emphasises  the  challenges  in  diagnosis,  treatment  and  prognosis  associated  with  this  rare  occurrence.